Polyolefin composite diaphragm for lithium battery as well as preparation method and application of polyolefin composite diaphragm

By adding a functional polymer material to the extraction drying process of the wet polyethylene partition production line to form a bonding function layer, the problem of complexity and cost of the existing lithium battery diaphragm production process is solved. Effect.

CN119381698AActive Publication Date: 2025-01-28YINGKOU KANGHUI PETROCHEM
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411459218.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2025-01-28
Estimated Expiration
2044-10-18

AI Technical Summary

Technical Problem

The existing lithium battery separator production process is complex and requires complicated coating processes, resulting in high production costs and complex process debugging, and thickening of the coating increases the internal resistance of the battery.

Method used

Add a functional polymer material to the extraction drying process of the wet polyethene partial membrane production line. The bonding function layer is formed by extracting and drying, eliminating the coating process.

Benefits of technology

With the case of not changing the existing wet polyolefin septum production line, prepare a polyolefin composite diaphragm with a bonding function layer, reduce production costs, simplify the process, and improve the infiltration and stability of the diaphragm.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005091394970000081
    Figure BDA0005091394970000081
  • Figure BDA0005091394970000091
    Figure BDA0005091394970000091
Patent Text Reader

Abstract

The invention belongs to the technical field of lithium ion battery diaphragms, and particularly discloses a polyolefin composite diaphragm for a lithium battery as well as a preparation method and application of the polyolefin composite diaphragm. When the polyolefin composite diaphragm provided by the invention is prepared, the bonding functional layer can be formed without a coating process, the thickness of the film is reduced, the adverse effect on the performance of the diaphragm caused by thickening the diaphragm by a coating is avoided, and the wettability of the polyolefin diaphragm can be improved due to the existence of the bonding functional layer. Besides, the coupling agent is added into the raw materials, so that the diaphragm can be endowed with stable and firm polar sites, the binding force between the functional polymer material and the polyolefin matrix is enhanced, and the formed binding functional layer is fixed on the surface of the diaphragm and is not easy to peel and fall off. According to the diaphragm preparation process provided by the invention, the preparation of one kind of coating films can be realized almost without modifying an existing wet-process polyolefin diaphragm production line, so that the process can be simplified, the enterprise load and the production cost can be greatly reduced, and the diaphragm preparation process has a good application prospect and economic value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium ion battery separators, and in particular relates to a polyolefin composite separator for lithium batteries and a preparation method and application thereof. Background Art

[0002] At present, the wet-process polyolefin diaphragm used in commercial lithium batteries is prepared through two major processes: a wet-process polyolefin diaphragm production line and a coating production line. The wet-process polyolefin diaphragm production line mainly uses polyolefin and white oil as raw materials, and dichloromethane as an extractant. The raw materials are prepared into polyolefin diaphragms through melt extrusion, cooling casting, sheet transverse and longitudinal stretching, extraction and drying, and secondary stretching. After the diaphragm is prepared, the coating production line needs to first prepare the coating slurry (including polymer materials such as polyvinylidene fluoride PVDF, polymethyl methacrylate PMMA, polyacrylonitrile PAN, polyvinyl alcohol PVA, etc.), and then use a coating machine to coat the wet-process polyolefin diaphragm, so that the slurry is evenly attached to the surface of the polyolefin diaphragm to increase the adhesion between the diaphragm and the electrode, ensure the consistency of the thickness of the battery cell, thereby improving the interface performance of the battery, and then dry it to obtain a coated diaphragm.

[0003] In order to simplify the production process, new synchronous online coating equipment is also available on the market, and the coating process is directly added after the secondary stretching process of the wet polyolefin diaphragm production line. However, it requires major changes to the existing wet polyolefin diaphragm production line, and the process debugging is complicated, and it is difficult to achieve the expected convenient and efficient coating effect. Secondly, although the coating diaphragm can improve the liquid retention rate of the diaphragm and the safety of the battery to a certain extent, the coating itself will increase the thickness of the diaphragm, thereby increasing the internal resistance of the battery. If there is an inorganic material in the coating, the interface compatibility between it and the organic material is poor, and it is also prone to problems such as coating powder falling. To solve this problem, Chinese patent CN109860473B (Yinlong New Energy) provides a method for preparing a lithium-ion battery diaphragm, mixing the coating slurry with a polyethylene solution, first hot pressing to obtain a flat film, and then cooling the casting, biaxial stretching, extraction and drying treatment in turn to obtain a battery diaphragm. This method only relies on the traditional wet polyolefin diaphragm production line to prepare a composite diaphragm, and the process is simple, but there are also problems such as the coating material affecting the performance of the diaphragm. Therefore, there is an urgent need to develop a new polyolefin composite separator for lithium batteries and a preparation method thereof. Summary of the invention

[0004] 1. Technical issues to be resolved

[0005] The technical problem to be solved by the present invention is to provide a polyolefin composite diaphragm for lithium batteries and a preparation method thereof. The polyolefin composite diaphragm with an adhesive functional layer can be prepared only through a wet diaphragm production line, eliminating the complicated coating process and greatly reducing the production cost.

[0006] (II) Technical solution

[0007] In order to solve the above technical problems, the present invention adopts the following technical solutions:

[0008] A polyolefin composite diaphragm for lithium batteries, the preparation method of the diaphragm comprising: adding a functional polymer material to an extractant in an extraction and drying process, drying after extraction to remove the extractant, and fixing the functional polymer material in the diaphragm to form a bonding functional layer; and no coating process is performed after the diaphragm is prepared.

[0009] As a preferred embodiment of the present invention, the functional polymer material includes but is not limited to one or more of polymethyl methacrylate (PMMA), polyacrylonitrile (PAN), polyvinyl alcohol (PVA), triacetyl cellulose (TCA), styrene-butadiene rubber (SBR), polyvinylidene fluoride (PVD), etc. When there are more than or equal to two types, they can be mixed in any proportion.

[0010] Specifically, the mass ratio of the functional polymer material to the extractant is 5-20:80-95.

[0011] As a preferred embodiment of the present invention, the extractant includes but is not limited to dichloromethane. The extractant is mainly used to extract the plasticizer (such as white oil) to form the membrane micropores.

[0012] As a preferred embodiment of the present invention, the extraction and drying process is multi-stage extraction, and the functional polymer material is added in the latter stage of the extraction. For example, the extraction and drying process is provided with 8 extraction tanks, and the functional polymer material can be added to the extractant (such as dichloromethane) of the last extraction tank or the last two extraction tanks.

[0013] As a preferred embodiment of the present invention, the preparation method of the diaphragm includes: mixing polyolefin and plasticizer and then melt-extruding, and sequentially cooling the cast sheet, primary stretching, extraction drying, and secondary stretching to obtain a polyolefin composite diaphragm for lithium batteries.

[0014] Specifically, the mass ratio of the polyolefin to the plasticizer is 15-35:65-85.

[0015] Specifically, the polyolefin includes but is not limited to one or more of polyethylene, polypropylene, etc. The weight average molecular weight of the polyethylene is 300,000-3,000,000.

[0016] Specifically, the plasticizer includes but is not limited to white oil.

[0017] Specifically, the raw materials for preparing the diaphragm include, in addition to polyolefin and plasticizer, a coupling agent, and the amount of the coupling agent is 0.5wt%-3wt% of the mass of the polyolefin.

[0018] Specifically, the coupling agent includes but is not limited to one or more of a silane coupling agent, a titanate coupling agent, an aluminate coupling agent, etc. Among them, the titanate coupling agent is such as isopropyl tri(dioctyl pyrophosphate acyloxy) titanate, and the aluminate coupling agent is such as distearoyloxyisopropoxy aluminate.

[0019] When an aluminate coupling agent is used, it is preferably added in the latter section of melt extrusion, and the extruder process parameter Q / NS value is set to <4.5. Since the aluminate coupling agent is prone to self-crosslinking under high temperature conditions, it not only affects the uniform dispersion of the aluminate coupling agent, but also causes pinholes in the diaphragm, affecting the safety of the lithium-ion battery. Therefore, the focus of adding the aluminate coupling agent is to reduce its residence time in the (twin-screw) extruder. Adjustments need to be made from the following two aspects: (1) Add the aluminate coupling agent in the latter section of the extruder; (2) Set the extruder process parameter Q / NS value (extrusion volume / screw speed value) to less than 4.5. The smaller the Q / NS, the shorter the residence time of the aluminate coupling agent in the extruder.

[0020] Specifically, the technical parameters of the melt extrusion are: temperature 180-220°C.

[0021] Specifically, the technical parameters of the cooling slab are: cooling roller temperature 5-35°C.

[0022] Specifically, the one-time stretching includes longitudinal stretching and transverse stretching in sequence. The technical parameters of the longitudinal stretching are: preheating and stretching temperature 90-130°C, cooling temperature 30-70°C, and stretching ratio 3-20 times; the technical parameters of the transverse stretching are: preheating, stretching, and shaping temperature 99-140°C, and stretching ratio 3-20 times.

[0023] Specifically, the secondary stretching is transverse stretching, and the technical parameters of the transverse stretching are: preheating, stretching, and shaping temperature 99-140° C., and a stretching ratio of 3-20 times.

[0024] A method for preparing a polyolefin composite diaphragm for a lithium battery comprises the following steps:

[0025] The polyolefin and the plasticizer are mixed and melt-extruded, and the polyolefin composite diaphragm for lithium battery is obtained by cooling the cast sheet, primary stretching, extraction drying, and secondary stretching in sequence;

[0026] Functional polymer materials are added to the extractant in the extraction and drying process, and the extractant is removed by drying after extraction, and the functional polymer materials are fixed in the diaphragm to form a bonding functional layer; no coating process is performed after the diaphragm is prepared.

[0027] As a preferred embodiment of the present invention, the mass ratio of the polyolefin to the plasticizer is 15-35:65-85.

[0028] Specifically, the polyolefin includes but is not limited to one or more of polyethylene, polypropylene, etc. The weight average molecular weight of the polyethylene is 300,000-3,000,000.

[0029] Specifically, the plasticizer includes but is not limited to white oil.

[0030] As a preferred embodiment of the present invention, the raw materials for preparing the diaphragm include, in addition to polyolefin and plasticizer, a coupling agent, and the amount of the coupling agent is 0.5wt%-3wt% of the mass of the polyolefin.

[0031] Specifically, the coupling agent includes but is not limited to one or more of a silane coupling agent, a titanate coupling agent, an aluminate coupling agent, etc. Among them, the titanate coupling agent is such as isopropyl tri(dioctyl pyrophosphate acyloxy) titanate, and the aluminate coupling agent is such as distearoyloxyisopropoxy aluminate.

[0032] When an aluminate coupling agent is used, it is preferably added in the latter section of melt extrusion, and the process parameter Q / NS value of the extruder is set to be less than 4.5.

[0033] As a preferred embodiment of the present invention, the technical parameters of the melt extrusion are: temperature 180-220°C.

[0034] As a preferred embodiment of the present invention, the technical parameters of the cooling slab are: the cooling roller temperature is 5-35°C.

[0035] As a preferred embodiment of the present invention, the one-time stretching includes longitudinal stretching and transverse stretching in sequence. The technical parameters of the longitudinal stretching are: preheating and stretching temperature 90-130°C, cooling temperature 30-70°C, and stretching ratio 3-20 times; the technical parameters of the transverse stretching are: preheating, stretching, and shaping temperature 99-140°C, and stretching ratio 3-20 times.

[0036] As a preferred embodiment of the present invention, the functional polymer material includes but is not limited to one or more of polymethyl methacrylate (PMMA), polyacrylonitrile (PAN), polyvinyl alcohol (PVA), triacetyl cellulose (TCA), styrene-butadiene rubber (SBR), polyvinylidene fluoride (PVDF), etc. When there are more than or equal to two types, they can be mixed in any proportion.

[0037] Specifically, the mass ratio of the functional polymer material to the extractant is 5-20:80-95.

[0038] As a preferred embodiment of the present invention, the extractant includes but is not limited to dichloromethane. The extractant is mainly used to extract the plasticizer (such as white oil) to form the membrane micropores.

[0039] As a preferred embodiment of the present invention, the extraction and drying process is multi-stage extraction, and the functional polymer material is added in the latter stage of the extraction. For example, the extraction and drying process is provided with 8 extraction tanks, and the functional polymer material can be added to the extractant (such as dichloromethane) of the last extraction tank or the last two extraction tanks.

[0040] As a preferred embodiment of the present invention, the technical parameters of the transverse stretching are: preheating, stretching, and shaping temperature 99-140° C., and a stretching ratio of 3-20 times.

[0041] The invention discloses an application of a polyolefin composite diaphragm for lithium batteries in the preparation of lithium-ion batteries.

[0042] (III) Beneficial effects

[0043] The preparation method of the polyolefin composite diaphragm for lithium battery provided by the present invention focuses on the extraction and drying process of the wet polyolefin diaphragm production line. The oil film passes through multiple extraction tanks to extract the plasticizer (such as white oil) by the extractant (such as dichloromethane). The present invention adds a certain amount of functional polymer material (selected from one or more of PMMA, PAN, PVA, TCA, SBR, PVDF) to the extractant in the latter stage of extraction. Since these polymer materials can be dissolved by dichloromethane, dichloromethane containing polymer materials will remain inside and on the surface of the extracted film. After drying, the dichloromethane volatilizes and the polymer material is evenly fixed inside and on the surface of the film to form a functional layer with adhesion. The functional layer can replace the sticky coating prepared by the coating process, so the complicated coating process can be omitted, greatly reducing the production cost. For production companies, simultaneous online coating of coating production lines and wet-process diaphragm production lines requires high equipment investment and production costs. The preparation process provided by the present invention can realize the preparation of a type of coating film with almost no need to modify the existing wet-process polyolefin diaphragm production line, which not only simplifies the process, but also greatly reduces the company's burden and production costs.

[0044] The polyolefin composite diaphragm for lithium batteries provided by the present invention can form a sticky functional layer without going through a coating process during preparation, and the film thickness is reduced, thereby avoiding the adverse effect of the thickening of the coating on the performance of the diaphragm. At the same time, the presence of the adhesive functional layer can improve the wettability of the polyolefin diaphragm. The present invention also utilizes the characteristics that the long-chain alkane group in the coupling agent is soft and non-polar, and has a high compatibility with the long carbon chain of the polyolefin. In the melt extrusion process, the mixing and shearing can be physically entangled to form a tight connection, so that the coupling agent is evenly distributed in the polyolefin matrix, and the polar groups thereon can also be evenly distributed on the surface of the polyolefin diaphragm, giving the diaphragm a stable and firm polar site, thereby enhancing the bonding force between the functional polymer material and the polyolefin matrix, so that the formed sticky functional layer is fixed to the surface of the diaphragm and is not easy to peel off.

[0045] The modified polyolefin separator provided by the present invention can be used for preparing lithium ion batteries, has simple production process, strong operability, is easy to carry out industrial production, and has good application prospects and high economic value. DETAILED DESCRIPTION

[0046] The technical scheme of the present invention will be clearly and completely described below in conjunction with specific embodiments, comparative examples and experimental examples. Those skilled in the art should understand that the following embodiments and experimental examples are only used to illustrate the technical scheme and technical effects of the present invention and should not be regarded as any limitation on the protection scope of the present invention. Based on the following embodiments, other technical schemes obtained by ordinary technicians in the field without paying creative labor, such as technical schemes obtained after modification, deformation or simple replacement, all belong to the protection scope of the present invention.

[0047] Unless otherwise specified, the raw materials, reagents, equipment, etc. used in the embodiments, comparative examples and experimental examples are all commercially available products.

[0048] Polyethylene powder, VH095, was purchased from Korea Petrochemical Corporation.

[0049] White oil was purchased from Zhejiang Zhengxin Petroleum Technology Co., Ltd.

[0050] Titanate coupling agent, NDZ-201 (isopropyl tri (dioctyl pyrophosphate acyloxy) titanate, molecular formula: C 51 H 112 O 22 P6Ti) was purchased from Nanjing Shuguang Chemical Co., Ltd.

[0051] Polyvinyl alcohol, PVA44-88, was purchased from Kuraray, Japan.

[0052] Example 1

[0053] This embodiment provides a polyolefin composite separator for a lithium battery, and the preparation method thereof comprises the following steps:

[0054] (1) Raw material melt extrusion and cooling casting

[0055] 30 parts of polyethylene, 70 parts of white oil and titanate coupling agent NDZ-201 (3% of the weight of polyethylene) were mixed, and the obtained mixture was heated and melted in a twin-screw extruder, and the melt was extruded through a T-die, and the composite sheet was obtained after cooling the cast sheet;

[0056] The technical parameters of melt extrusion are: temperature 200°C; the technical parameters of cooling the cast sheet are: cooling roller temperature 25°C.

[0057] (2) One-time stretching

[0058] The composite sheet obtained in step (1) is longitudinally stretched by longitudinal hot roller stretching, with the technical parameters being: preheating and stretching temperature of 100° C., cooling temperature of 50° C., and stretching ratio of 4 times, to obtain a longitudinally stretched film;

[0059] The longitudinally stretched film obtained above was then uniformly stretched transversely by a chain clamp method, with the technical parameters being: preheating, stretching, and shaping temperature of 120° C., and a stretching ratio of 4 times, to obtain a biaxially stretched film.

[0060] (3) Extraction and drying

[0061] The fully stretched film obtained in step (2) is immersed in a dichloromethane extraction tank for multi-stage extraction to separate the plasticizer white oil in the film body. In the last stage of extraction, a dichloromethane solution containing a functional polymer material polyvinyl alcohol (the mass ratio of polyvinyl alcohol to dichloromethane is 5:95) is used. After drying, a composite film with a uniform bonding functional layer is obtained.

[0062] (4) Secondary stretching

[0063] The composite film obtained in step (3) is uniformly stretched again in the horizontal stretching machine, and the technical parameters are: preheating, stretching, and shaping temperature are 120° C., and the stretching ratio is 4 times, to obtain a polyolefin composite diaphragm for lithium batteries.

[0064] This embodiment also provides an application of a polyolefin composite separator for a lithium battery in the preparation of a lithium ion battery.

[0065] Example 2-3

[0066] The method for preparing a polyolefin composite separator for a lithium battery in Example 2-3 is basically the same as that in Example 1, except that the mass ratios of polyvinyl alcohol to dichloromethane in step (3) are 10:90 and 20:80, respectively.

[0067] In other embodiments of the present invention, the raw materials and amounts for preparing the polyolefin composite diaphragm for lithium batteries can be arbitrarily selected or taken within a given range. For example, polypropylene is selected to replace polyethylene, and the mass ratio of polyethylene to white oil is set to 15:85; an aluminate coupling agent (such as distearoyloxyisopropoxyaluminate) is selected to replace the titanate coupling agent; polymethyl methacrylate PMMA is selected to replace polyvinyl alcohol PVA, which hardly affects the overall performance of the diaphragm.

[0068] In other embodiments of the present invention, the parameter conditions involved in the method for preparing a polyolefin composite diaphragm for a lithium battery can take any value within a given range. For example, the stretching ratios of the longitudinal stretching and the transverse stretching in one stretching are both set to 3.5 times, which has almost no effect on the overall performance of the diaphragm.

[0069] Comparative Example

[0070] The method for preparing a lithium-ion battery separator in the comparative example is basically the same as that in Example 1, except that in step (3), the functional polymer material polyvinyl alcohol is not added to the extractant for the last stage of extraction, and only dichloromethane is used for extraction.

[0071] Experimental example

[0072] Experimental method: The lithium ion battery separators prepared in Examples 1-3 and Comparative Example were tested for thickness and water contact angle, and the peeling force between the bonding functional layer and the polyethylene separator was tested. The test results are shown in Table 1 below.

[0073] Table 1 Lithium-ion battery separator test results

[0074]

[0075]

[0076] It can be seen from Table 1 that, compared with the existing composite separators, the thickness of the polyolefin composite separators for lithium batteries prepared in Examples 1-3 is significantly reduced, and is only slightly thicker than the comparative example.

[0077] Compared with the comparative example, the water contact angle of the polyolefin composite separator for lithium batteries prepared in Examples 1-3 is greatly reduced, indicating that the bonding functional layer can improve the wettability of the polyethylene separator.

[0078] Compared with the comparative example, the peeling force between the bonding functional layer and the polyethylene matrix in the polyolefin composite separator for lithium batteries prepared in Examples 1-3 is increased, indicating that the functional layer is not easy to peel off.

[0079] Conclusion: It can be seen from the above experimental results that the polyolefin composite diaphragm for lithium batteries provided by the present invention can form an adhesive functional layer without going through a coating process during preparation, and the film thickness is reduced, avoiding the adverse effect of the coating coating on the performance of the diaphragm due to the thickening of the diaphragm, and the presence of the adhesive functional layer can improve the wettability of the polyolefin diaphragm. In addition, the present invention can give the diaphragm a stable and firm polar site by adding a coupling agent to the raw material, enhance the bonding force between the functional polymer material and the polyolefin matrix, and make the formed adhesive functional layer adhere to the surface of the diaphragm, which is not easy to peel off, thereby improving the overall stability of the diaphragm.

[0080] The diaphragm preparation process provided by the present invention can realize the preparation of a type of coating film with almost no need to modify the existing wet polyolefin diaphragm production line, which can not only simplify the process but also greatly reduce the enterprise load and production cost, and has good application prospects and high economic value.

[0081] Although the technical scheme and technical effects of the present invention have been described in detail above by means of general description, specific embodiments and experimental examples, for those skilled in the art, any modification, replacement or improvement made without departing from the spirit of the present invention shall fall within the protection scope of the present invention.

Claims

1. A polyolefin composite diaphragm for lithium battery, characterized in that: The preparation method of the diaphragm comprises: adding a functional polymer material to an extractant in an extraction and drying process, drying after extraction to remove the extractant, and fixing the functional polymer material in the diaphragm to form a bonding functional layer; and no coating process is performed after the diaphragm is prepared.

2. The polyolefin composite separator for lithium battery according to claim 1, characterized in that: The functional polymer material includes but is not limited to one or more of polymethyl methacrylate, polyacrylonitrile, polyvinyl alcohol, cellulose triacetate, styrene-butadiene rubber, and polyvinylidene fluoride; And / or, the mass ratio of the functional polymer material to the extractant is 5-20:80-95; And / or, the extractant includes but is not limited to dichloromethane.

3. The polyolefin composite separator for lithium battery according to claim 1, characterized in that: The extraction and drying process performs multi-stage extraction, and functional polymer materials are added in the latter stage of the extraction.

4. The polyolefin composite separator for lithium battery according to claim 1, characterized in that: The preparation method of the diaphragm comprises: mixing polyolefin and plasticizer and then melt-extruding, and sequentially performing the steps of cooling the cast sheet, primary stretching, extraction drying, and secondary stretching to obtain a polyolefin composite diaphragm for lithium battery.

5. A method for preparing a polyolefin composite separator for a lithium battery according to any one of claims 1 to 4, characterized in that: The method comprises the following steps: The polyolefin and the plasticizer are mixed and melt-extruded, and the polyolefin composite diaphragm for lithium battery is obtained by cooling the cast sheet, primary stretching, extraction drying, and secondary stretching in sequence; Functional polymer materials are added to the extractant in the extraction and drying process, and the extractant is removed by drying after extraction, and the functional polymer materials are fixed in the diaphragm to form a bonding functional layer; no coating process is performed after the diaphragm is prepared.

6. The preparation method according to claim 5, characterized in that: The mass ratio of the polyolefin to the plasticizer is 15-35:65-85; And / or, the polyolefin includes but is not limited to one or both of polyethylene and polypropylene; And / or, the plasticizer includes but is not limited to white oil.

7. The preparation method according to claim 5, characterized in that: The raw materials for preparing the diaphragm also include a coupling agent, and the amount of the coupling agent is 0.5wt%-3wt% of the mass of the polyolefin; The coupling agent includes, but is not limited to, one or more of a silane coupling agent, a titanate coupling agent, and an aluminate coupling agent.

8. The preparation method according to claim 5, characterized in that: The technical parameters of the melt extrusion are: temperature 180-220°C; And / or, the technical parameters of the cooling cast sheet are: cooling roller temperature 5-35°C; And / or, the one-time stretching includes longitudinal stretching and transverse stretching in sequence; the technical parameters of the longitudinal stretching are: preheating and stretching temperature 90-130°C, cooling temperature 30-70°C, and stretching ratio 3-20 times; the technical parameters of the transverse stretching are: preheating, stretching, and shaping temperature 99-140°C, and stretching ratio 3-20 times; And / or, the secondary stretching is transverse stretching, and the technical parameters of the transverse stretching are: preheating, stretching, and shaping temperature 99-140° C., and a stretching ratio of 3-20 times.

9. The preparation method according to claim 5, characterized in that: The functional polymer material includes but is not limited to one or more of polymethyl methacrylate, polyacrylonitrile, polyvinyl alcohol, cellulose triacetate, styrene-butadiene rubber, and polyvinylidene fluoride; And / or, the mass ratio of the functional polymer material to the extractant is 5-20:80-95; and / or, the extractant includes but is not limited to dichloromethane; And / or, the extraction and drying step is performed in multiple stages, and the functional polymer material is added in the latter stage of the extraction.

10. Use of the polyolefin composite separator for lithium battery according to any one of claims 1 to 4 in the preparation of lithium ion batteries.

Citation Information

Patent Citations

  • Preparation method of lithium-ion battery separator

    CN109860473B

  • Method of preparing polythene fibre with high surface adhesion ultra-high relative molecular mass

    CN101109113A

  • Preparation method of lithium ion battery separator

    CN108172745A

  • Preparation method of high-wettability polyolefin diaphragm for lithium ion battery

    CN115084776A

  • Preparation method of aluminate coupling agent modified lithium ion battery polyolefin diaphragm

    CN118539086A